Analisis Kemampuan Literasi Numerasi dalam Menyelesaikan Soal Cerita Matematika Siswa Sekolah Dasar - Endradewi, Cindy Fatimah; Muhtarom, Muhtarom; Setyowati, Rina Dwi (Cetta: Jurnal Ilmu Pendidikan, 2025)
Numeracy literacy is an important basic skill in learning mathematics, especially at the primary school level. It includes the skills of understanding, interpreting and solving mathematical problems linked to real-life contexts. However, many students still face difficulties in solving math story problems due to weak understanding of the content of the problem and inability to choose the right solution strategy. This study aims to analyze the numeracy literacy skills of fourth grade students in solving mathematical story problems and identify the factors that influence it. The method used was descriptive qualitative with the subject of 15 students at SD Negeri Pohijo 01. Three students were selected as samples based on high, medium, and low ability categories. The results showed that 20% of students were in the high, 47% medium, and 33% low categories. Students with high ability are able to understand the contents of the problem and develop strategies systematically. Students in the medium category can understand some of the contents of the problem, but are not consistent in choosing the solution steps. Meanwhile, students in the low category had difficulty in reading the text, made mistakes in choosing calculation operations, and tended to answer based on guesses. Factors that influence students' abilities include reading skills, experience of contextual problems, learning strategies, and learning motivation. This study emphasizes the importance of strengthening critical reading and applying contextual approaches in mathematics learning.